Sigmund Freud : the basics - Sayers, Janet (New York : Routledge, 2020)
"Sigmund Freud: The Basics is an easy-to-read introduction to the life and ideas of Sigmund Freud, the founder of psychoanalysis and a key figure in the history of psychology. Janet Sayers provides an accessible overview of Freud's early life and work, beginning with his childhood. Her book includes the stories of his most famous patients: Dora, Little Hans, the Rat Man, Judge Schreber and the Wolf Man. It also discusses Freud's key ideas such as the Oedipus complex and psychoanalytic treatment. Sayers then covers Freud's later work, with a description of his observations about depression, trauma and the death instinct, as well as his 1923 theory of the id, ego, and superego. The book includes a glossary of key terms and concludes with examples of how psychoanalysis has been applied to the study of art, literature, film, anthropology, religion, sociology, gender politics and racism. Sigmund Freud: The Basics offers an essential introduction for students from all backgrounds seeking to understand Freud's ideas and for general readers with an interest in psychology. For those already familiar with Freudian ideas, it offers a helpful guide to their interdisciplinary applications and context not least today"--
OCLC-licensed vendor bibliographic record.
Keywords: Freud, Sigmund, -- 1856-1939.; Psychotherapy -- History; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Mental Health